Phylogenetic analysis of haemagglutinin gene deciphering a new genetically distinct lineage of canine distemper virus circulating among domestic dogs in India. Issue 3 (27th February 2019) - Bhatt, M.; Rajak, K. K.; Chakravarti, S.; Yadav, A. K.; Kumar, A.; Gupta, V.; Chander, V.; Mathesh, K.; Chandramohan, S.; Sharma, A. K.; Mahendran, K.; Sankar, M.; et al.
Summary: Canine distemper (CD) is one of the highly contagious and invariably fatal viral diseases of dogs and other carnivores. Despite the widespread use of modified live vaccines to control CD, the prevalence of disease has increased at an alarming rate in recent years. Although a number of factors may be ascribed for vaccine failure, antigenic differences among the vaccine and wild‐type strains have gained the interest of researchers. Considering the high genetic variability of haemagglutinin gene (H gene) and its role in eliciting the immune response to canine distemper virus (CDV), we have generated nine full‐length CDV H gene sequences from infected dogs including three vaccinated cases. Bayesian analysis was performed using 102 full‐length H gene nucleotide sequences over a time frame of 76 years (1940–2016) from 18 countries. The time to the most recent common ancestor (tMRCA) of CDV was estimated to be 1696 AD. Phylogenetic reconstruction clustered Indian wild‐type viruses into a distinct monophyletic group clearly separated from the previously established CDV lineages. This signifies the presence of a novel genetic variant (proposed as "Lineage India‐1/Asia‐5") circulating among dog population in India. To investigate the importance of substitutions at amino acid residues 530 and 549 of CDV H protein in determining the host switches from canid to non‐canid hosts, we analysed 125 H gene sequences including nine sequences generated in this study. Selection pressure analysis and analysis of amino acid sequences revealed a trend towards adaptation of 549H variants in non‐canid hosts although no role of G/E530R/D/N substitution could be identified. This is the first comprehensive study about the nature and ecology of CDV circulating among dog population in India. Outbreaks in vaccinated animals as observed in this study have raised a concern towards the effectiveness of current vaccine strains warranting detailed investigation.